2019
DOI: 10.3892/ijo.2019.4701
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for the anticancer activity of aspirin and salicylates

Abstract: Epidemiological studies indicate that long-term aspirin usage reduces the incidence of colorectal cancer (CRC) and may protect against other non-CRC associated adenocarcinomas, including oesophageal cancer. A number of hypotheses have been proposed with respect to the molecular action of aspirin and other non-steroidal anti-inflammatory drugs in cancer development. The mechanism by which aspirin exhibits toxicity to CRC has been previously investigated by synthesising novel analogues and derivatives of aspirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 100 publications
1
23
0
1
Order By: Relevance
“…Therefore, prior to surgery, patients had less excretion of salicyluric acid, which is the glycine conjugate of salicylic acid, a component of aspirin. Some studies have suggested that aspirin has a chemoprotective role in colorectal cancer, where salicyluric acid and its derivatives are metabolized by colon cells and exert a protective effect [ 71 , 72 ]. One compound found to be upregulated pre- and post-surgery, L-pyroglutamic acid, was also upregulated in CRC and advanced adenoma compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prior to surgery, patients had less excretion of salicyluric acid, which is the glycine conjugate of salicylic acid, a component of aspirin. Some studies have suggested that aspirin has a chemoprotective role in colorectal cancer, where salicyluric acid and its derivatives are metabolized by colon cells and exert a protective effect [ 71 , 72 ]. One compound found to be upregulated pre- and post-surgery, L-pyroglutamic acid, was also upregulated in CRC and advanced adenoma compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Salicylates and their derivatives are potent and widely used nonsteroidal anti‐inflammatory drugs with a wide spectrum of modulating activities, comprising inhibition of cyclooxygenases and of NF‐kB , allosteric activation of AMP kinase (AMPK) , alteration of mTOR signaling , perturbation of EGFR internalization , and inhibition of CBP/p300 acetyltransferase activity . Recently, we showed that salicylates also inhibit signaling by HMGB1 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, small interfering RNA (siRNA) transfection has been reported to downregulate BIRC7/Livin expression towards apoptotic induction in CRC in vitro and in vivo [60]. Aspirin reduces CRC growth via different mechanisms such as, inhibition of cyclooxygenase-2, dysregulation of NFκβ and Wnt-β-catenin signalling pathways, activation of EGFR pathway, host immune response modulation and up-regulation of tumour suppression genes [61][62][63]. Our findings using the TCGA showed a higher expression of BIRC7/Livin in Whites and Asians compared with African-Americans.…”
Section: Plos Onementioning
confidence: 99%